Ground- and excited-state vibrational coherence dynamics in bacteriorhodopsin probed with degenerate four-wave-mixing experiments - Kraack, Jan Philip; Buckup, Tiago; Hampp, Norbert; Motzkus, Marcus (ChemPhysChem, 2011)
Vibrational coherence dynamics in the all-trans retinal chromophore in Bacteriorhodopsin (BR) are investigated by means of temporally and spectrally resolved degenerate four-wave-mixing experiments. The coherence dynamics depend on the excitation wavelength when BR samples are excited at different wavelengths in a spectral range between 520 nm to above 620 nm. The trends in the dynamics observed by tuning of the excitation wavelength allow an assignment of the wave packet dynamics to ground- and excited-state potential energy surfaces. Specifically, the intensity of so-called “out-of-plane” modes of polyene-chain substituents increases for excitation wavelengths near 500 nm. It is shown that this is consistent with the assignment of out-of-plane modes to excited-state coherence dynamics. Moreover, intense low-frequency coherence dynamics around 200 cm−1 are observed for signal detection in two different spectral regions of excited-state absorption. These modulations are assigned to excited-state dynamics due to the observed dependence on the excitation wavelength. In addition, we show that generally high-frequency modes (>1010 cm−1) originate from wave packet motion in the electronic ground state of all-trans retinal.